Can counter-stereotypes boost flexible thinking?. (March 2013) - Gocłowska, Małgorzata A.; Crisp, Richard J.; Labuschagne, Kirsty
To reduce prejudice psychologists design interventions requiring people to think of counter-stereotypes (i.e., people who defy stereotypic expectations— a strong woman, a Black President ). Grounded in the idea that stereotypes constrain the ability to think flexibly, we propose that thinking of counter-stereotypes can have benefits that extend beyond the goal of prejudice reduction—in particular to tasks measuring cognitive flexibility and creative performance. Findings supported this conjecture. In Experiment 1 priming a gender counter-stereotype enhanced cognitive flexibility. This effect could not be attributed to changes in mood. In Experiment 2, using a gender-independent manipulation, priming various social counter-stereotypes brought a boost to creative performance. We discuss implications of these extended benefits of counter-stereotypic thinking for developing future prejudice-reduction interventions.